An Alongshore Momentum Budget Over a Fringing Tropical Fore‐Reef. Issue 11 (6th November 2018) - Arzeno, Isabella B.; Collignon, Audric; Merrifield, Mark; Giddings, Sarah N.; Pawlak, Geno
Abstract: Existing momentum budgets over coral reefs have predominantly focused on cross‐reef dynamics, lacking analysis of alongshore processes. To complement existing cross‐reef research and enhance our understanding of forcing variability at the semidiurnal period, this study examines the σ –coordinate, depth‐averaged alongshore momentum budget over a fore‐reef as a function of tidal phase. The observations were gathered over a 3‐week timespan, between the 12‐ and 20‐m isobaths of a Hawaiian fringing reef system, focusing on two moorings on the 12‐m isobath, where median drag coefficients estimated from log fits are C D =0.0080[−0.002, +0.004] and C D =0.0023[−0.0006, +0.0009]. Analysis at one location shows that the unsteadiness, barotropic pressure gradient, and bottom drag are equally important, and their combination is sufficient to close the momentum budget. However, bottom drag is less important at the second mooring; the difference between unsteadiness and pressure gradient suggests that advective acceleration plays a significant role. Plain Language Summary: Coral reefs are important, productive ocean ecosystems that are highly influenced by hydrodynamic forcing. Although a lot of research has been done to understand what forces drive the flow across tropical reefs (from offshore to onshore), less is known about the forces that drive flow parallel to the shoreline (alongshore). Here we study the physical dynamics over a coral reef in Hawai'i and determine that two primary forces drive the alongshore flow acceleration. One of the dominant forces is the drag exerted by the bottom reef, since coral are rougher than typical sandy coastal beds. The other dominant force is the pressure gradient, associated with the difference in sea level set up by the tide. The tidal cycle and the resulting flow response has important implications for the reef environment, with relevance for reef biology and, eventually, for ecosystem management policies. Key Points: A tidal alongshore momentum budget is estimated over a tropical fringing coral reef system Unsteadiness, barotropic pressure gradient, and bottom drag play a dominant role on the fore‐reef Advective acceleration can be of similar magnitude and necessary for budget closure